2002
DOI: 10.1080/13607860220142486
|View full text |Cite
|
Sign up to set email alerts
|

Formal and informal care for people with dementia: Factors associated with service receipt

Abstract: Details of service receipt by 132 people diagnosed with dementia and their carers were collected in South London (boroughs of Lewisham, Camberwell, Southwark and Croydon), a geographical area served by several health and social care providers. The data collected included the Caregiver Activity Survey, which details the informal care given. This paper reports the formal and informal services received by the people with dementia at entry to the study. The amount of time spent on specific caring tasks by all info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 21 publications
8
53
0
Order By: Relevance
“…A British study by Schneider et al (2002) found that co-residing carers of moderate to severely demented people spent on average 10.5 h per day (h/d) informal care. These findings are in concordance with our results when comparing with the more severe stages of dementia, CDR 2 and 3, where the average in those stages combined is approximately 10 h/d for all subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A British study by Schneider et al (2002) found that co-residing carers of moderate to severely demented people spent on average 10.5 h per day (h/d) informal care. These findings are in concordance with our results when comparing with the more severe stages of dementia, CDR 2 and 3, where the average in those stages combined is approximately 10 h/d for all subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Others have studied predictors of home help utilization restricted to whether the subjects did or did not receive public home help rather than the number of hours of help received (Larsson et al, 2004). Although there are several studies describing the amount of formal and informal care, most of these studies have included selected populations such as clinical samples or convenient samples (Schneider et al, 2002;Wimo et al, 2002). Others have tried to quantify the amount of formal and informal care by deciding that certain tasks (such as dressing/ undressing) would be given, for example five hours per week (Johansson and Thorslund, 1992), or by providing information on the number and regularity of care-giving contacts rather than the duration of these contacts (RIS MRC CFAS, 1998).…”
Section: Introductionmentioning
confidence: 97%
“…Caregiver burden is closely aligned to the goals of many interventions and is associated with negative health outcomes in carers of people with common conditions, such as dementia, stroke, and cancer [8,10,11]. Moreover, perceived burden had been shown to predict anxiety and depression in carers of patients with these conditions [12e14].…”
Section: Introductionmentioning
confidence: 99%
“…In each study, we converted these reports to the number of hours spent caring per week. Based on the estimate that a dementia caregiver spends around 40 h per week providing care duties on average, we used a threshold of ≥40 care hours to identify caregivers with a substantial caring role in order to create a dichotomous variable harmonized over the studies [36,37]. …”
Section: Methodsmentioning
confidence: 99%